Effect of Training and Motivation on Employees Performance of The Environment and Forestry Department of Riau Province - Raden Rudi Alhempi; Sudirman; Bambang Supeno (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2021)
Training and motivation can be maintained and can have an effect on improving employee performance, but in reality the training and motivation of employees is still not able to improve the performance of the employees of the Environment and Forestry Department of Riau Province. This is still a lack of both technical and non-technical training intended for employees who can improve performance and motivation at work. This study aims to determine the effect of training and motivation on improving the performance of employees of the Environment and Forestry Office of Riau Province. This type of quantitative research with a sample of 87 people.The analysis technique uses descriptive analysis, validity and reliability test, normality test, multicollinearity test, autocorrelation test, linearity test, with multiple linear regression approach using SPSS 19 IBM. The results of the study partially show that there is a positive and significant effect between training on employee performance. There is a positive and significant effect between motivation on employee performance. Simultaneously there is a positive and significant effect between training and motivation on employee performance.